The impact of depressive and bipolar symptoms on socioeconomic status, core symptoms, function and severity of fibromyalgia. (31st July 2015) - Gota, Carmen E.; Kaouk, Sahar; Wilke, William S.
Abstract: Aim: To evaluate the prevalence of depressive and bipolar symptoms in a cohort of consecutive fibromyalgia (FM) patients seen in a tertiary care center and to determine the relationship between depressive and manic symptoms with FM symptoms, socioeconomic status, severity and function. Methods: Three hundred and five FM patients were enrolled; demographic, clinical and questionnaire data were collected. Depressive symptoms were measured by the Patient Health Questionnaire (PHQ‐9), manic symptoms by the Mood Disorders Questionnaire (MDQ). Results: The FM cohort had the following characteristics: age 43.53 (11.7) years; 86.5% white; 82.7% female; PHQ‐9 ≥ 10, 59.7%, mean 11.9 (7.3); no depression 11.4%, mild 29.1%, moderate 27.5%, moderate severe 17.7%, severe 14%; anxiety 41.6%; 21.3% had either an MDQ score ≥ 7 and/or reported a past diagnosis of bipolar disorder (BD). Increasing levels of depression severity, as well as a positive screen for BD were significantly associated with increasing prevalence and severity of FM symptoms, longer duration of morning stiffness, and increased severity of FM. Increasing levels of depression were significantly associated with increase in prevalence of reported past sexual abuse, and a decline in socioeconomic status, including higher disability and unemployment rates. Conclusion: Patients with severe FM disease activity, high load of symptoms, prolonged morning stiffness, increased disability, lower socioeconomic status and those who take a lot of medications for FM should be evaluated for depressive and manic symptoms.